Forest education as contribution to education for environmental citizenship and non-anthropocentric perspectives. Issue 9 (1st August 2022) - Kowasch, Matthias; Oettel, Janine; Bauer, Nicole; Lapin, Katharina
Abstract: Forest ecosystems play a fundamental role in mitigating global environmental changes. The development of environmentally sound behavior, and inter- and intragenerational equity can help counteract these global changes. One type of formal and non-formal environmental education is forest education, which aims to promote the achievement of sustainable development in forest-related ecosystems. We conducted an empirical study among forest educators in Austria, using a mixed-method approach, to investigate the potential of forest education to promote education for environmental citizenship. Our findings suggest that forest education and encounters with nature can lead to increased self-responsibility and contribute to critically reflect experience-based changes in behaviour. In conclusion, forest education is a useful tool for environmental citizenship education that contributes to improved understanding of forest ecosystems and non-anthropocentric perspectives for future development. However, forest education lacks funding, integration into formal education curricula, and the harmonization of framework conditions in non-formal education.